1995
DOI: 10.1182/blood.v86.4.1464.bloodjournal8641464
|View full text |Cite
|
Sign up to set email alerts
|

Numerical chromosome aberrations are present within the CD30+ Hodgkin and Reed-Sternberg cells in 100% of analyzed cases of Hodgkin's disease [see comments]

Abstract: In Hodgkin's disease, cytogenetically aberrant clones have been demonstrated in a minority of cases studied. In the remaining cases, only normal metaphases have been found, but it is questionable whether normal karyotypes actually correspond to the pathognomonic Hodgkin and Reed-Sternberg (HRS) cells. Numerical aberrations could be studied by fluorescence in situ hybridization (FISH). However, in Hodgkin's disease, the percentage of tumor cells is mostly below the detection limit of FISH, which is near 1%. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(39 citation statements)
references
References 13 publications
1
36
0
2
Order By: Relevance
“…In one case of HD, some chromosome aberrations were constant throughout the whole tumor-cell population, whereas other chromosomes showed highly variable copy numbers. For example, the H-RS cells had 2 to 8 copies of chromosome 1 (Weber-Matthiesen et al, 1995). There was considerable variability in the chromosome numbers in each chromosome and case, thus demonstrating karyotype instability to be an in vivo phenomenon of H and RS cells (Weber-Matthiesen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one case of HD, some chromosome aberrations were constant throughout the whole tumor-cell population, whereas other chromosomes showed highly variable copy numbers. For example, the H-RS cells had 2 to 8 copies of chromosome 1 (Weber-Matthiesen et al, 1995). There was considerable variability in the chromosome numbers in each chromosome and case, thus demonstrating karyotype instability to be an in vivo phenomenon of H and RS cells (Weber-Matthiesen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…By fluorescence immunophenotyping and interphase cytogenetic analysis (FICTION), hybridization signals can be evaluated selectively within the CD30 ϩ H and RS cell population (Weber-Matthiesen et al, 1995). Using centrometric DNA probes of the chromosome 1, 8, 12, 15, 17, X and Y, we thus analyzed 30 cases with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous cytogenetic and immunological characterization of neoplastic cells in haematological malignancies enables the assignment of clonal chromosome abnormalities to a specific cell lineage. Few studies have shown lineage restriction of specific clonal aberrations in myelo-and lymphoproliferative disorders by simultaneous analysis of cell surface or cytoplasmic immunological markers and chromosome analysis by FISH (Kibbelaar et al, 1992;Garcia-Marco et al, 1994;Weber-Matthiesen et al, 1992, 1995aZhang et al, 1996). FICTION techniques enable simultaneous assessment of both immunophenotype and genotype in a single cell.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical or structural chromosomal alterations within H/RS cells have been described in 30 cases of cHD by Weber-Matthiesen and colleagues. 2 Nevertheless, the pathogenetic role of chromosomal aberrations detected in H/RS cells is unclear; chromosomal alterations are shown to be mostly non-clonal within the H/RS population of a given case and karyotype changes in cHD are not specific for H/RS cells.…”
mentioning
confidence: 99%